Sustainable urban water management through the lens of community – a photostory exercise in metropolitan Adelaide. Issue 2 (2nd April 2016) - Wu, Zhifang; Keremane, Ganesh; McKay, Jennifer
ABSTRACT: This article reports the process and results of a study in which community was engaged to examine emotional resonance around the concept of urban water. The study was an important component of a legal and governance study, which aimed to identify the governance challenges and potential solutions to support the implementation of an integrated urban water management strategy in metropolitan Adelaide. The team used photostory method for this purpose, which included participants taking photos and interpreting their meanings through a process of reflection. The dialogue around the photos, the diaries, and the group discussions demonstrates how this method can provide a greater depth of understanding of how water saving and sustainable water management are rationalised and how they become shared experiences. The article concludes by discussing some of the limitations of the method and providing suggestions for using this method to engage a community in research.